1973
DOI: 10.2307/957308
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Lukacic

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To ensure accuracy and consistency the project began by coding speeches analysed and discussed in detail by O'Loughlin and Grant. 26 When the two researchers responsible for coding gained the same results as O'Loughlin and Grant and each other the initial coding of the 1988 speeches began. Three speeches were chosen at random and the researchers coded them individually.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…To ensure accuracy and consistency the project began by coding speeches analysed and discussed in detail by O'Loughlin and Grant. 26 When the two researchers responsible for coding gained the same results as O'Loughlin and Grant and each other the initial coding of the 1988 speeches began. Three speeches were chosen at random and the researchers coded them individually.…”
Section: Methodsmentioning
confidence: 96%
“…We began with the State of the Union speech of 1988 for two reasons: It provides a continuation from the O'Loughlin and Grant study that concluded with 1987, and it provides a benchmark year of a presidency firmly attached to the Cold War geopolitical code before the subsequent years of dynamism that we focus upon. 24 The texts of the speeches were downloaded from the website of The American Presidency project housed at University of California Santa Barbara between August 2007 and March 2008. 25 The texts were coded for word content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation